A statistical characterisation of the distribution of a cloud of space debris after a break-up in orbit. (August 2019) - Thomasson, D.; Deleflie, F.; Petit, A.
Abstract: This paper aims at proposing a new way of statistically characterising the spatial distribution of a cloud of space debris generated by a fragmentation in orbit, by using a family of functions that is well-known in applied mathematics. Such a family can be very convenient to describe through a few parameters the main features affecting the dynamical evolution of the whole cloud, and the mutual distance between objects within the cloud, at different epochs. The tested population of space debris is supposed to be a configuration of points resulting from the realisation of a point process and what we call "exploratory tools" from spatial statistics are applied to it. The role played by some parameters driving the breakup or the dynamical model on the statistical results is investigated with examples based on Fengyun-1C-like and Molniya-like cases. Highlights: A new statistical tool is experimented to analyze the spatial distribution of a cloud of space debris. The influence of model parameters on the statistical results is studied. Greatest changes in the results are induced by the strength and initial conditions of the event. Fragments eccentricity has a great influence on the spatial distribution evolution of the cloud.